APPLICATION OF MULTIDIMENSIONAL CLASSIFICATION TOOLS FOR INDUSTRIAL POLICY MEASURES SUBSTANTIATION: CASE OF IMDUSTRIAL CLUSTER - Svetlana Smirnova (Krymskij Naučnyj Vestnik, 2015)
The modeling stage of development of industrial cluster is significant for the formation of industrial policy and institutional conditions for economic growth. The work deals with the modeling stage of the life cycle of industrial cluster, the results of testing applied to the petrochemical industry of the Russian Federation. Also, highlights issues approbation of this method by applying the results of simulation as a training set for building the classification tree and the interpretation of the results to justify investment and infrastructure projects.